Customer repurchase intentions on Ramadhan iftar buffet in 4 & 5 star hotels / Fatmawati Abdul Fatah - Abdul Fatah, Fatmawati (2016)
Behavioral intention is imperative and relevant for a restaurant industry because repurchase intention of discontented customers are significantly lower than the intentions of satisfied customers. Behavioral intentions toward any restaurant may be favorable or unfavorable depending on the satisfaction and have been an accurate predictor of actual behavior. An increased of overall satisfaction can lead to positive behavioral intention toward repurchase as well as actual re-patronization. In contrast, unfavorable behavioral intentions, based on the perceived poor quality food and service may include intent to switch to other service restaurants provider, intent to reduce money expenditure with the restaurants, intent to complain and even the intent to take action. Literature demonstrates the importance of retaining customers and its impact on profitability. In line with this, many argued that the cost of retaining, keeping the existing or loyal restaurant customers are much lower than attracting the new ones. In this sense, regardless of whatever types of restaurant businesses either ethnic, casual, upscale including hotel restaurant, it is indispensable to retain and create loyalty atmosphere among the customers in order to survive the intense competition among the restaurant operations. In this context, restaurant attributes such quality and variety of food, price together with operating attributes like location,accessibility, promotion just to name a few may have strong connection with satisfaction thus lead to restaurant customer revisit intention. This study is empirically examining and understanding the effect of menu attributes, hotel operating attributes, brand image, and customer satisfaction on customer repurchase intention of Ramadhan iftar buffet in four and the five star hotels. To integrate and entwined the findings the quantitative through customers approach was opted. Through a self-administered survey among the Ramadhan iftar buffet customers at selected four to five star hotels at Kuala lumpur, 215 questionnaires were successfully collected. With the application of various statistical analyses ranging from descriptive and inferential statistics used to answer the objectives, research questions and hypotheses some important findings pertaining to the issues investigated was significantly obtained. The customers generally put high priority on the Iftar menu attributes emphasizing on taste of the food and variety of food choices. Hotel operating attributes on the other hand prioritize ample hotel parking space, fast service and accessibility. The respondents are also found to be willing to spend their money in the 4 and 5 star hotel due to the image of prestigious hotel with high hotel reputation. The brand image also toward some extent influence the customer satisfaction as some hotel brand image such as high star rated, established hotel brand and prestigious hotel are the one with high satisfaction rating. In term of repurchase intention, majority of the customers show good indication of returning back to the hotel to experience the Ramadhan iftar buffet. The finding of this study has given consequences not only to the customer but to the hotel as well.